The Influence of Weaving Activities on Self-Identity Development in Kindergarten: Exploring Early Childhood Enrichment - Ihsanti, Nura; Amelia, Lina; Muthmainnah, Muthmainnah (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
The fine motor development of children aged 5-6 years at the ABA Kindergarten Kedai Manggeng Aceh Barat Daya experiences several obstacles in the development of their fine motor skills, and this is indicated by the child's hands still being stiff when holding a pencil and cutting not according to the pattern. So, this research aims to determine the effect of weaving activities with coconut leaves on the development of the identity of children aged 5-6 years at the ABA Kedai Manggeng Kindergarten, Aceh Barat Daya. This quantitative research uses a pre-experimental design through approach one group pre-test post-test design. The sample used was all group B1 students (29 people) taken using random sampling techniques. Data collected based on observation results obtained an average value pretest amounted to 52.06%, and the average value posttest obtained 75.10%, so the resulting normality test is 0.233 > 0.05. Based on this data, the value of tcount┬á> ttable┬áis 16.949 > 1.04841, So it can be stated that Ha┬áaccepted and HO. Based on these data, it can be concluded that weaving activities can influence the development of children's identity at the Kedai Manggeng ABA Kindergarten, Aceh Barat Daya.┬á.┬á